2000
DOI: 10.1021/ar990006x
|View full text |Cite
|
Sign up to set email alerts
|

Organic Synthesis and Chemical Ecology

Abstract: The roles of organic synthesis in chemical ecology are discussed, with many examples. The structure, including the absolute configuration, of a semiochemical (signal substance) can be established by enantioselective synthesis. Only through synthesis can a semiochemical be obtained in an amount sufficient for decisive biological evaluation. Rigorous enantioselective synthesis of semiochemicals to provide their pure enantiomers has shown that they are not always enantiomerically pure. Synthesis of the stereoisom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(25 citation statements)
references
References 64 publications
0
24
0
Order By: Relevance
“…(16) In 1994, Aldrich and co-workers identified methyl 2,6,10-trimethyldodecanoate (15) and methyl 2,6,10-trimethyltridecanoate (16) as components of the maleproduced sex pheromones of the stink bugs, Euschistus heros and Euschistus obscurus. 62,63 The same compounds were later found in headspace volatiles from Brazilian male bug, Piezodorus guildinii, but the biological roles of these compounds in the species have not been delineated.…”
Section: Cis-2-isopropenyl-1-methylcyclobutaneethanol (14) (Grandisol)mentioning
confidence: 99%
See 1 more Smart Citation
“…(16) In 1994, Aldrich and co-workers identified methyl 2,6,10-trimethyldodecanoate (15) and methyl 2,6,10-trimethyltridecanoate (16) as components of the maleproduced sex pheromones of the stink bugs, Euschistus heros and Euschistus obscurus. 62,63 The same compounds were later found in headspace volatiles from Brazilian male bug, Piezodorus guildinii, but the biological roles of these compounds in the species have not been delineated.…”
Section: Cis-2-isopropenyl-1-methylcyclobutaneethanol (14) (Grandisol)mentioning
confidence: 99%
“…8,9 Several reviews have been described focusing on many aspects of pheromone science. [10][11][12][13][14][15][16][17] Rapid progress has been made in research on insect pheromones in Brazil during the last decade, including the identification, synthesis, biosynthesis and field evaluation of the bioactive compounds and continuing attempts are expected in the coming years. 18 The growth of the field in Brazil naturally led to the organization of national meetings in the area.…”
Section: Introductionmentioning
confidence: 99%
“…The optical purity and the absolute configurations of the resolved 16 were determined by a chiral HPLC, and comparisons of their optical rotations were made with those in the literature. 17 After de-N-benzoylation of optically pure 16, the resulting amines (17) were reacted with 2,3-anthracenedicarboxylic anhydride 4 to give optically pure A. Similarly, optically pure A′ was also prepared by the reaction of optically pure 17 and commercially available 2,3-naphthalenedicarboxylic anhydride (Scheme 1).…”
Section: (R)-and (S)-2-(23-anthracenedicarboximido)-1-propyl Alcohomentioning
confidence: 99%
“…Studies of Mori on the relationship between optical purity and biological activity of insect pheromones, [2][3][4] which revealed that the biological activities of some insect pheromones were dramatically changed by their optical purities, have demonstrated the importance of determining the absolute configuration and accurate optical purity of biologically active compounds. However, the most widely used diastereomer method for the discrimination of enantiomers has a problem in that it is very difficult, or even impossible, to discriminate diastereomers having chiral centers separated by more than four bonds.…”
mentioning
confidence: 99%
“…If there is no stereoisomer to inhibit the bioactivity of other isomer(s), we can expect good bioassay results even with the stereoisomeric mixture of a pheromone. 7) Indeed, in the case of G. tachinoides, a racemic and diastereomeric mixture of 11,23-dimethylheptatriacontane was active as the sex stimulant against male ‰ies. 8) As shown in Scheme 1, our synthetic plan for 1 and 2 is very simple.…”
mentioning
confidence: 99%